Commonsense consequentialism : wherein morality meets rationality - Portmore, Douglas W. (New York : Oxford University Press, 2011)
This is a book about morality, rationality, and the interconnections between the two. In it, Portmore defends a version of consequentialism that both comports with our commonsense moral intuitions and shares with consequentialist theories the same compelling teleological conception of practical reasons.
Includes bibliographical references and index.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 17, 2012).
Keywords: Consequentialism (Ethics); Practical reason